The Factors Affect the Implementation of English Teaching Strategies before and during Covid- 19 Pandemic Era - Geminastiti Sakkir; Amirullah Abduh (PT ARRUS Intelektual Indonesia, 2022)
This study was conducted to know and identify the challenges faced by teachers in teaching English in the current curriculum change. The research method that will be used is the descriptive qualitative method. The subjects are 102 teachers in SMA/MA/SMK/equivalent in South Sulawesi Province. Data obtained from essay questions were analyzed through qualitative data analysis techniques through coding. The results of the analysis were in the form of a description of the factors that affect the implementation of English teaching strategies before and during the Covid-19 Pandemic era. This description will be useful for learners, teachers, policymakers, and foreign language learning theorists. The results of the study indicate that many factors affect the teacher’s strategies in teaching English in the current curriculum change (before and during the Pandemic Covid-19 era). The factors come from students’ conditions, teachers’ conditions, school conditions, environmental conditions, materials conditions, learning process, administration process, and technology implementation.